APLIKASI NAVIGASI LOKASI POM BENSIN DI JAKARTA BERBASIS ANDROID - Hartono, Foeng; Sevani, Nina (Teknik dan Ilmu Komputer, 2013)
Gas stations are public facilities crucial for motorists. Mobile applications installed in smartphones such as GPS and integrated internet connection can help motorists Â find the nearest gas station in a fast and easy way. Mobile application used in this research is based on Android platform considering the androidâs popularity. This application can be employed to locate the gas stationÂ around its userâs location and to navigate them to the nearest one. Finding out the nearest location route can minimize the risk of running out of fuel. Users can also maximize the use of smartphone by using this application. A series of steps taken in this research include literature study, observation, flowchart design, Unified Modeling Language (UML), and interface and database design. The application was tested by distributing questionnaires to the users.Â Â Keywords: location, gas station, GPS, android,Â mobile